Singleton pregnancies after in vitro fertilization in Estonia: a register-based study of complications and adverse outcomes in relation to the maternal socio-demographic background - Kaja Rahu; Kärt Allvee; Helle Karro; Mati Rahu (BMC Pregnancy and Childbirth, 2019)
Abstract Background An increased risk of adverse conditions related to in vitro fertilization (IVF) pregnancies has been repeatedly reported. Our study aimed to summarize outcome differences between pregnancies after IVF and after spontaneous conception (SC) in Estonia. Methods Data on all liveborn singletons to primiparas women aged 25–40 years during the period 2005–2014 were obtained from the Estonian Medical Birth Registry. There were 1778 and 33,555 newborns in the IVF and SC cohort, respectively. The relative risk of pregnancy-related complications and adverse pregnancy outcomes in the IVF cohort in comparison with the SC cohort was quantified by prevalence proportion ratios (RR) with 95% confidence intervals (CI) using modified Poisson regression models adjusted for maternal age, education, ethnicity, marital status and study period. Results The cohort of IVF singletons experienced a higher risk of preterm birth (RR 1.51; 95% CI 1.28–1.78), iatrogenic preterm birth (RR 1.62; 95% CI 1.32–1.98), very preterm birth (RR 1.49; 95% CI 1.00–2.23), low birthweight (RR 1.47; 95% CI 1.20–1.80), congenital anomalies (RR 1.51; 95% CI 1.08–2.11), and admission to a neonatal intensive care unit (RR 1.13; 95% CI 1.01–1.26). Somewhat elevated risk of spontaneous preterm birth did not reach statistical significance (RR 1.32; 95% CI 0.97–1.80). IVF mothers were at increased risk of placenta previa (RR 7.15; 95% CI 4.04–12.66), placental abruption (RR 2.12; 1.43–3.14) and cesarean section (RR 1.28; 95% CI 1.20–1.37). The risk of pre-eclampsia was borderline (RR 1.25; 95% CI 0.98–1.59). Adjustment for maternal age attenuated the associations between IVF and adverse outcomes. Maternal education, ethnicity and marital status had no effect on the magnitude of the risk estimates. Conclusions The increased risk of pregnancy-related complications and adverse pregnancy outcomes was observed in the Estonian cohort of IVF singletons in comparison with the cohort of SC singletons. The relative risk estimates grew with maternal age but were not influenced by the maternal education, ethnicity and marital status. To monitor the efficacy and safety of the used assisted reproductive technology, a specialized country-wide register should be created in Estonia.